Master of Faculty of Computer Science and Information Technology - Universiti Malaysia Sarawak, Faculty of Computer Science and Information Technology (Universiti Malaysia Sarawak (UNIMAS), 2020)
Faculty of Computer Science and Information Technology Bachelor's Degree Certificate yr 2020 for 387 Students